2015 IEEE MTT-S International Conference on Microwaves for Intelligent Mobility (ICMIM) 2015
DOI: 10.1109/icmim.2015.7117925
|View full text |Cite
|
Sign up to set email alerts
|

A method for interference cancellation in automotive radar

Abstract: In this paper a method for interference detection and cancellation for automotive radar systems is proposed. With the growing amount of vehicles equipped with radar sensors, interference mitigation techniques are getting more and more important to maintain good interoperability. Based on the time domain signal of a 76 GHz chirp sequence radar the interfering signals of FMCW radar sensors are identified. This is performed by image processing methods applied to the time-frequencyimage. With the maximally stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…This is done based on the high power and the short duration of the interference in [76]. Other approaches apply matched signal transforms [77] or image processing methods [78] to detect interference. It was shown that OFDM interference is very difficult to distinguish from thermal noise in the spectrum of FMCW receivers, making a detection more problematic [79].…”
Section: Interference Detectionmentioning
confidence: 99%
“…This is done based on the high power and the short duration of the interference in [76]. Other approaches apply matched signal transforms [77] or image processing methods [78] to detect interference. It was shown that OFDM interference is very difficult to distinguish from thermal noise in the spectrum of FMCW receivers, making a detection more problematic [79].…”
Section: Interference Detectionmentioning
confidence: 99%
“…[4]. Multiple countermeasures already exist to this kind of interferences, like time domain signal repair [5], digital beamforming [6], [7], or frequency hopping [8].…”
Section: Introductionmentioning
confidence: 99%
“…2 shows only the velocity 5 m/s; the bicycle cannot be detected anymore. Instead of sharp notching, a window function can be used to smoothen the junction between signal and gap [6]. Fig.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Regarding time domain radar signals, interferences typically show up as time-limited artifacts with a very high amplitude. Therefore, their occurrence can be detected with power detectors or matched filters [5], but also methods from image processing have been adapted [6]. After detection, an often recommended technique is to simply remove the interfered samples from the signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation